Perancangan Sudu Turbin Angin Berkecepatan Rendah Dengan Variasi Jenis Airfoil Menggunakan Metode Momentum Elemen Sudu - , YEZID ROKHMATULAH, Ir. Kutut Suryopratomo, M.T., M.Sc. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Wind turbine is a device used to convert wind energy into mechanical energy or electrical energy. Wind turbines are designed with special conditions such as wind speed wind velocity profile environment and surroundings. Therefore we designed a wind turbine blades for wind conditions in Indonesia, which has a relatively low wind speeds. The design conducted using blade element momentum method which is a combination of momentum theory and blade element theory. Our wind turbine is designed with a blade length of 2 meters. Some airfoil chosen to look for value Coefficient of Power (Cp) and selected airfoil with the largest value of Cp. This validation is performed in the design to determine how close the theory which used in the design with reality. Existing turbine is used as an object of validation. retrieval and processing of data in the form of data dimensions and operation data obtained from wind turbines deviation value is 9.7%. Output of the design process is a two-dimensional form Variable torsional angle and wide-chord. Eventually airfoil-types of S2091 101-83 chosen because it produces the highest value of Cp.